The functional divergence of homologous GPAT9 genes contributes to the erucic acid content of Brassica napus seeds - Hongbo Liu; Jinbo Zhu; Bingxin Zhang; Qingyang Li; Cui Liu; Qian Huang; Peng Cui (BMC Plant Biology, 2024)
Abstract Background The early allopolyploid Brassica napus was a hybrid of two Brassica species, that had undergone a whole genome duplication event followed by genome restructuring, including deletions and small scale duplications. A large number of homologous genes appeared functional divergence during species domestication. Due to the high conservation of de novo glycerolipid biosynthesis, multiple homologues of glycerol-3-phosphate acyltransferases (GPATs) have been found in B. napus. Moreover, the functional variances among these homologous GPAT-encoding genes are unclear. Results In this study, four B. napus homologous genes encoding glycerol-3-phosphate acyltransferase 9 (BnaGPAT9) were characterized. Although a bioinformatics analysis indicated high protein sequence similarity, the homologues demonstrated tissue-specific expression patterns and functional divergence. Yeast genetic complementation assays revealed that BnaGPAT9-A1/C1 homologues but not BnaGPAT9-A10/C9 homologues encoded functional GPAT enzymes. Furthermore, a single nucleotide polymorphism of BnaGPAT9-C1 that occurred during the domestication process was associated with enzyme activity and contributed to the fatty acid composition. The seed-specific expression of BnGPAT9-C1 1124A increased the erucic acid content in the transformant seeds. Conclusions This study revealed that BnaGPAT9 gene homologues evolved into functionally divergent forms with important roles in erucic acid biosynthesis.